Sex-specific regulation of the cortical transcriptome in response to sleep deprivation - Shi, Tianyi; Shah, Ishani; Dang, Quang; Taylor, Lewis; Jagannath, Aarti (Frontiers in Neuroscience, 2024)
Multiple studies have documented sex differences in sleep behaviour, however, the molecular determinants of such differences remain unknown. Furthermore, most studies addressing molecular mechanisms have been performed only in males, leaving the current state of knowledge biased towards the male sex. To address this, we studied the differences in the transcriptome of the cerebral cortex of male and female C57Bl/6 J mice after 6 h of sleep deprivation. We found that several genes, including the neurotrophin growth factor Bdnf, immediate early genes Fosb and Fosl2, and the adenylate cyclase Adcy7 are differentially upregulated in males compared to females. We identified the androgen-receptor activating transcription factor EZH2 as the upstream regulatory element specifying sex differences in the sleep deprivation transcriptome. We propose that the pathways downstream of these transcripts, which impact on cellular re-organisation, synaptic signalling, and learning may underpin the differential response to sleep deprivation in the two sexes.